Common Risk Factors in Equity Markets - Victoria Atanasov (Tinbergen Institute, 2014)
Empirical measures of world consumption growth risk have failed to rationalize the cross-section of country equity returns. We propose a new factor, termed the global consumption factor, to explain the patterns in risk premiums on international equity markets. We identify this factor as the difference between the return on a portfolio of equity market indices with high consumption growth rates and the return on a portfolio of equity market indices with low consumption growth rates. We show that the global consumption factor accounts for about 70% of the cross- sectional variation in equity returns from 47 developed and emerging market countries over a four-decade period. Our risk factor reflects changes in the cross-country consumption dispersion and commands a significant premium to compensate investors for taking on common macroeconomic risks. Empirically, we find that high consumption growth economies have considerably higher consumption dispersion risk than low consumption growth economies, and this can explain their higher average returns.
Keywords: G11; G12; 330; stock returns; asset pricing; macroeconomic risks; consumption dispersion